Biomedical applications of sharkskin mimicked polymeric membranes - Rostami, Sabra. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2022., 2022)
Infection is one of the biggest challenges of implantable biomaterials. The diffi culty of eliminating implant-associated infection imposes a huge burden on the patient's life quality aside from the considerable financial cost of the treatment. Thus, effective approaches must be explored to design biomaterials with enhanced antibacterial ac tivity. Sharks have been investigated via biomimetic and bioinspiration approaches and discoveries have shown that sharkskin possesses antibacterial effects due to the reduced drag force on the skin whilst swimming which is because of their skin’s surface microstructure. In this thesis the antibacterial properties of sharkskin mimicked poly meric membranes in static conditions, with and without the aid of antibacterial and bactericidal chemicals was studied. The aim was to understand the adhesion behav ior of both bacteria and mammalian cells onto the biomimicked polymeric membranes and how the surface topography affected these properties. Moreover, the impact of surface topography on drug release and bactericidal activity of these membranes was investigated by examining the physicochemical, antibacterial, and cytocompatibility properties of fabricated membranes. In vitro experiments were conducted to evaluate cellular responses of mammalian cells along with bactericidal properties using human keratinocyte (HaCaT), mouse fibroblast (L929), and human dermal primary fibroblast (HDFa) cell lines as model cells and Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus bacterial strains as model bacteria species. The results presented in this thesis show that sharkskin polymeric membranes have great potential for reduc ing bacterial biofilm formation most probably via preventing bacterial adhesion. Also, the cell adhesion on these membranes can be enhanced via chemical modifications.|Keywords: Sharkskin, Biomimetic, Antibacterial, Cytocompatibility, Chitosan, Graph ene Oxide, Ampicillin Sodium Salt, Caffeic Acid Phenethyl Ester.
Keywords: Biomimetic materials.; Antibacterial agents.; Chitosan -- Biotechnology.